Association between white blood cell count and coronary artery bypass graft failure: an individual patient data analysis of clinical trials - Kevin R. An; Sigrid Sandner; Joyce Peper; Yanzai Zhou; Jurrien M. ten Berg; Lamia Harik; Yunpeng Zhu; Laura M. Willemsen; Qiang Zhao; Björn Redfors; Subodh Verma; Mario F. L. Gaudino (Journal of Cardiothoracic Surgery)
Abstract Background Baseline systemic inflammation is associated with worse long-term outcomes after coronary artery bypass grafting [CABG], but the mechanisms of this association are unclear. This study aims to explore the association between pre-operative white blood cell [WBC] count and CABG graft failure. Methods We pooled individual patient data from two randomized clinical trials with systematic CABG graft imaging. The primary analysis was the association between pre-operative WBC count and graft failure, as a continuous variable, at the time of imaging after CABG, using mixed-effects multivariable logistic regression models. Results Overall, 910 patients and 2,036 grafts were included in the analysis [1,120 saphenous vein grafts, 828 left internal thoracic arteries, 76 right internal thoracic arteries, and 12 radial arteries]. The median time to imaging was 1.01 [interquartile range (IQR), 0.99;1.03] years and the median pre-operative WBC count was 7.1 [IQR, 6.0;8.4] x 109/L. There was no association between WBC count and graft failure at both the patient and the individual graft level [adjusted odds ratio (aOR) 1.07 (95% confidence interval (CI), 0.98;1.17), p = 0.11 and aOR 1.09 (95% CI, 0.91;1.30), p = 0.37], respectively. When evaluated as a dichotomous variable [≥ 11 vs. < 11 × 109/L] and by quartile, WBC count was not associated with graft failure at the patient and individual graft levels. Conclusion In this pooled analysis of individual patient data from two randomized clinical trials, WBC count was not associated with graft failure after CABG. The reported association between inflammation and CABG is likely mediated through other mechanisms, such as native coronary artery disease progression. Impact on daily practice The lack of a clear association between WBC count and graft failure suggests that pre-operative WBC count should not be routinely used as a predictor of graft failure after CABG.